(untitled) (Mustansiria Dental Journal, 2018)
Etching and re-etching are frequently done technique to alter the tooth surface and makes it more receptive to adhesion. This study was done to assess the effect of reetching technique on bond strength to enamel, dentin and dentino-enamel junction. 60 extracted human upper premolars teeth were collected cleaned, sectioned at the level of cervical line, embedded in acrylic block exposing certain grounded flat surface of the crown and divided into 2 groups: Group A (30 etched specimens) etched with total etch (37% phosphoric acid) for 15 sec. Group B (30 re-etched specimens) etched and re-etched with total etch (37% phosphoric acid). Both groups were subdivided into: Subgroup 1 10 enamel specimens Subgroup 2 10 dentin specimens Subgroup 3 10 dentino-enamel junction specimens A standardized cylinders of light cure composite resin were bonded, and the specimens were stored in deionized distilled water for 24 h. and testing was done with zwick test machine and statistically analyzed using analysis of variance test (ANOVA) and student t-test. The results showed non significant difference between all subgroups in group A(etching group) and between all subgroups in group A Vs. group B subgroup 2(reetched E), and showed a significant difference between all subgroups in group A Vs group B subgroup 3 (re- etched EDJ) and between group B sub1&2 (re-etched E & D) Vs group B sub 3 ( re-etched DEJ) ,furthermore there were a highly significant differences between all subgroups in group A Vs group B sub 2(re-etched D) and between group B sub 2(re-etched E) Vs groupB sub 2(re-etched D). Re-etching the enamel didn’t decrease the shear bond while re-etching dentin markedly decreased the bond strength. Further more re-etching the dentino-enamel junction lies in between.